MENYAKITI DIRI SENDIRI PADA KALANGAN REMAJA: Self Harm In Adolescents - Amseke, Fredericksen Victoranto; Sonia, Sonia; Naklui, Sisilia Susana (Yayasan Al-Amin Qalbu, 2026)
Self-harm is the act of intentionally harming oneself without suicidal intent, often as a way to cope with emotional pain or stress. Commonly occurring in adolescents, this behavior can signal a deeper mental health problem and requires attention and support for recovery. This study was conducted to clearly understand the reasons why adolescents engage in self-harm. The subjects studied were three adolescents, two girls and one boy, aged 18 to 21 years. This study used a descriptive qualitative method with data collection through interviews. The results showed that self-harm often appears as an unhealthy way to cope with severe emotional stress. The main findings revealed that self-harming behavior is influenced by three main factors: personal factors, family dynamics, and social relationships. Therefore, it can be concluded that self-harm is an expression of more complex emotional problems and requires a comprehensive treatment approach. Therefore, prevention and rapid intervention, along with a better understanding of self-harming behavior, are crucial to help adolescents deal with emotional stress in a positive way